7th International Symposium on Superalloy 718 and Derivatives (2010) 2010
DOI: 10.7449/2010/superalloys_2010_877_891
|View full text |Cite
|
Sign up to set email alerts
|

Microstructure Evolution in the Nickel Base Superalloy Allvac 718Plus®

Abstract: Nickel base superalloys experience significant changes of the microstructure during processing as well as in service. The mechanical properties are predominantly determined by microstructure parameters like grain size, γ′-precipitate diameter and volume fraction, etc. Thus, knowledge about the microstructure evolution during processing is a necessary prerequisite to employ novel alloys as Allvac®718Plus™ in service.In the present study, microstructure evolution during heat treatment in particular has been inve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 3 publications
1
10
1
Order By: Relevance
“…This confirmed findings of Xie et al [23] and Viskari et al, [4] who reported on the presence of a hexagonal Ni 3 Al 0.5 Nb 0.5 phase in 718Plus. This is in contrast to many other former studies [8,21,24] that described the grain boundary phase as δ phase like in alloy 718. This explained also, why the chemical composition of the grainboundary phase in 718Plus had often been found to be different from Ni 3 Nb with significant concentrations of Al and Ti.…”
Section: Introductioncontrasting
confidence: 95%
See 3 more Smart Citations
“…This confirmed findings of Xie et al [23] and Viskari et al, [4] who reported on the presence of a hexagonal Ni 3 Al 0.5 Nb 0.5 phase in 718Plus. This is in contrast to many other former studies [8,21,24] that described the grain boundary phase as δ phase like in alloy 718. This explained also, why the chemical composition of the grainboundary phase in 718Plus had often been found to be different from Ni 3 Nb with significant concentrations of Al and Ti.…”
Section: Introductioncontrasting
confidence: 95%
“…This explains, why a γ 00 phase was detected in this study in contrast to many former publications. [15][16][17][18][19][20][21] The γ 0 / γ 00 compounds are similar to the compact morphologies in alloy 718 that were characterized by Cozar and Pineau [7] and further investigated by He et al [27] The alloy IN706, which is also hardened by γ 0 precipitates, shows the same compounds of γ 0 and γ 00 phases. [29] Analogous to the precipitates of alloy 718, the γ 00 discs nucleate on the {001} γ/γ 0 interface planes because of the given crystal orientation relationship of (001) γ 00 ∥ {001} γ 0 , [100] γ 00 ∥ 〈001〉 γ 0 between both phases and the smaller lattice misfit between γ 00 and γ 0 compared with γ 00 and γ.…”
Section: Discussionsupporting
confidence: 56%
See 2 more Smart Citations
“…The principal difference in 718Plus chemistry is lower Ti-to-Al ratio as well as lower amount of Fe, which is replaced by the addition of Co and W. These modifications led to replacement of metastable c¢¢ main strengthening phase in IN718 with more stable c¢ phase in 718Plus that caused a increase in thermal stability up to 704°C. Other constituents of 718Plus microstructure are c matrix and precipitates of hexagonal g-Ni 3 Ti, g*-Ni 6 AlNb or Ni 6 (Al, Ti)Nb phases distributed mainly at the grain boundaries (Ref [6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%